Rockets R us [Russia launch industry]. - Cass, S.A.
In the four decades since Sputa, one rocket after another has punched through the skies above Baikonur Cosmodrome. But in the years following the collapse of the Soviet Union in December 1991, it looked as though Baikonur and the rest of the former Soviet space industry might pass into history, too. Nevertheless, the industry has survived; nearly every launch vehicle inherited from the Soviet Union by Russia and Ukraine is still in operation. By teaming up with marketing partners and investors abroad, Russian and Ukrainian rocket-building enterprises have even introduced new versions of their space boosters, mostly aimed at the commercial market, and have further upgrades in the pipeline. The ex-Soviet fleet ranges from the mammoth Proton heavy-lift vehicle to the versatile Zenit, which can be launched from a converted oil rig out at sea. This range and variety makes the former Soviet Union a strong competitor to the US and European launch industries
Keywords: Proton heavy-lift vehicle; Russia; Zenit; Investors; Launch vehicle; Marketing partners; Rocket launch industry; Rocket-building enterprises; Space boosters; Space industry